Pengaruh Pola Asuh pada Anak Broken Home Terhadap Kenakalan Remaja di MTs Bipda Sukajadi - Maulida Hasanah; Ika Sadra Dewi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Every parent has their own parenting style in educating their children, and this affects the child's development. Children's negative behavior can occur as a result of broken home parenting applied by their parents. Broken home parenting applied by parents can have a negative effect on children, including making them more free. Adolescence is a transitional period from childhood to adulthood or it can be said that adolescence is an extension of childhood, a transitional period where adolescents are in the process of fostering themselves while obtaining support and care from parents, the environment, society, and being independently responsible. This study aims to determine whether there is an influence of parenting patterns in broken home children on juvenile delinquency at MTs BIPDA SUKAJADI. The method in this study is quantitative research with the population being all students in grades VII and IX MTs. BIPDA SUKAJADI totaling 148 students. Sampling using random sampling technique which amounted to 50 students. This study uses a simple linear regression test. Based on the results of the study, it is known from the results of the regression coefficient value of -075 and a significant value of 0.611. This shows that there is an influence of parenting patterns in broken home children on juvenile delinquency at MTs BIPDA SUKAJADI.